1961
DOI: 10.1002/app.1961.070051709
|View full text |Cite
|
Sign up to set email alerts
|

Diazonium derivatives of cellulose as initiators of graft polymerization

Abstract: Cellulose p‐aminophenacyl ether (I) has been prepared from cotton and the partial p‐aminophenacyl ester of carboxymethyl cellulose (III) has also been prepared. Derivatives (I) and (III) have been diazotized and then used to initiate polymerization of acrylonitrile. In the presence of ferrous sulfate the polymerization proceeds to formation of a graft copolymer and no polyacrylonitrile homopolymer was detected. Attempts to graft styrene and vinyl acetate on the same derivatives were not successful. Thermal deg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1963
1963
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…In addition to peroxides, diazonium salts have also been introduced into the cellulose molecule as an initiating group. 94 This method involves the introduction of an aromatic amine onto the cellulose backbone, followed by its conversion to its corresponding diazonium salt. Upon heating, the diazonium salt decomposes to produce free radicals, leading to graft copolymerisation, when a suitable monomer is present.…”
Section: Direct Radical Formation On the Cellulose Backbone Via Chemi...mentioning
confidence: 99%
“…In addition to peroxides, diazonium salts have also been introduced into the cellulose molecule as an initiating group. 94 This method involves the introduction of an aromatic amine onto the cellulose backbone, followed by its conversion to its corresponding diazonium salt. Upon heating, the diazonium salt decomposes to produce free radicals, leading to graft copolymerisation, when a suitable monomer is present.…”
Section: Direct Radical Formation On the Cellulose Backbone Via Chemi...mentioning
confidence: 99%
“…Cellulose fibers have been graft copolymerized using various techniques in the past. Most of them are based on a “grafting-from” process, where radicals are formed along the polymer backbone either by various chemical initiators or by irradiation, followed by a free radical polymerization of vinyl monomers. In these methods, chain scission can occur and does not necessarily render the cellulose backbone intact .…”
Section: Introductionmentioning
confidence: 99%
“…Mino and Kaizermann (144) found that ceric ion redox systems gave high yields of copolymer, because the free-radical sites were generated mainly on the trunk polymer. Richards described, in 1961, several interesting approaches to grafting, using the ceric ion (145) and also diazonium cellulose derivatives (146) as initiators. He was able to graft acrylonitrile onto cellulose in this way.…”
Section: Resin-bonded Cellulose Separatorsmentioning
confidence: 99%
“…The graft copolymerization of monomers onto cellulose has been pursued most actively using methyl methacrylates and related monomers (126,148,150,151,(153)(154)(155). Styrene has been studied (146,156), as has vinylpyridine (157) and methylvinylpyridine (158).…”
Section: Resin-bonded Cellulose Separatorsmentioning
confidence: 99%